A low-cost cementite (Fe3C) nanocrystal@N-doped graphitic carbon electrocatalyst for efficient oxygen reduction. Issue 41 (1st October 2015) - Wu, Tianxing; Zhang, Haimin; Zhang, Xian; Zhang, Yunxia; Zhao, Huijun; Wang, Guozhong
Abstract : A core–shell structure Fe3 C nanocrystal@N-doped graphitic carbon (Fe3 C@NGC) nanocomposite was successfully fabricated, and used as an electrocatalyst with large surface area, exhibiting great potential for oxygen reduction reaction (ORR). Abstract : In this work, chitosan whiskers (CWs) were first extracted using low-cost and earth-abundant crab shells as materials by a series of chemical processes, and then assembled into chitosan whisker microspheres (CWMs) via a simple photochemical polymerization approach. Subsequently, a cementite (Fe3 C) nanocrystal@N-doped graphitic carbon (Fe3 C@NGC) nanocomposite was successfully fabricated by high temperature pyrolysis of CWMs adsorbed with ferric acetylacetonate (Fe(acac)3 ) at 900 °C. It was found that a suitable growth atmosphere generated inside CWMs during high temperature pyrolysis is critically important to form Fe3 C nanocrystal cores, concurrently accompanying a structural transformation from chitosan whiskers to mesoporous graphitic carbon shells with natural nitrogen (N) doping properties, resulting in the formation of a core–shell structure Fe3 C@NGC nanocomposite. The resulting samples were evaluated as electrocatalysts for oxygen reduction reaction (ORR). In comparison with sole N-doped graphitic carbon without Fe3 C nanocrystals obtained by direct pyrolysis of chitosan whisker microspheres at 900 °C (CWMs-900), Fe3 C@NGC showed significantly improved ORR catalytic activity. The tolerance to fuel cell molecules ( e.g., methanol) and the durability of Fe3 C@NGC are obviously superior to commercial Pt/C catalysts in alkaline media. The high ORR performance of Fe3 C@NGC could be due to its large surface area (313.7 m 2 g −1 ), a synergistic role of Fe3 C nanocrystals, N doping in graphitic carbon creating more catalytic active sites, and a porous structure of the nanocomposite facilitating mass transfer to efficiently improve the utilization of these catalytic active sites.